Literacy in a foreign language: the learning of French pronouns by ESL learners - Wong, Bee Eng; Lim, Sep Neo (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
This study investigates the French pronoun paradigm in the non-native grammars of adult university Ll (first language) Chinese speakers who have learnt English as a dominant L2 (second language) and French as a foreign language. Specifically the study seeks to identify the types of Interlanguage structures produced by LI Chinese speakers in their learning of French pronouns. A questionnaire was administered to obtain information about the learners' background and to select the sample for the study. The respondents selected for this study were twenty-three adult Ll Chinese speakers who were Bachelor of Arts (French) students at the Faculty of Modem Languages and Communication at Universiti Putra Malaysia. Three tasks were designed to collect the required data. The first was a Grammaticality Judgement Task where respondents judged and selected the correct pronouns in 75 French sentences. The second task which comprised 50 items required the respondents to replace noun phrases with the correct pronouns in French. This was a transformation task. The third task which comprised 50 items was a blank-filling task where respondents had to fill in each blank with the correct form of the pronoun in French. These tasks were administered over three sessions of about one hour each. The data indicate that some French pronouns were more problematic than others for the learners. An explanation is provided as to why this might be the case and what the findings mean in terms of literacy in a foreign language.